Manometry Optimized Positive Expiratory Pressure (MOPEP) in Excessive Dynamic Airway Collapse (EDAC). (October 2017) - Zafar, Muhammad A.; Mulhall, Aaron M.; Eschenbacher, William; Kaul, Ajay; Benzaquen, Sadia; Panos, Ralph J.
Abstract: Background: Positive expiratory pressure(PEP) breathing modalities are commonly prescribed in obstructive lung diseases, however practical methods of airway pressures(AP) quantification for therapeutic efficacy are lacking. Excessive dynamic airway collapse(EDAC) is characterized by expiratory central airway collapse leading to dyspnea and poor quality of life(QoL), with limited therapeutic options. Purpose: To measure AP and exertional dyspnea in EDAC patients during normal breathing and with use of pursed-lip breathing(PLB), nasal PEP device(nPEP), and oral-PEP valve(oPEP) during rest and exercise using an Esophageal Manometer. Methods: EDAC patients exercised on a bicycle ergometer sequentially using normal breathing, PLB, nPEP, and oPEP for five-minute intervals. AP's were measured by continuous topographic upper airway manometry. Pre- and post-exercise BORG dyspnea scores were recorded and QoL measured with the St. George's respiratory questionnaire(SGRQ-C). The most effective and patient-preferred PEP modality was prescribed for daily activities and SGRQ-C repeated after one week. Results: Three women with symptomatic EDAC participated. Expiratory laryngopharyngeal AP's during exercise with normal breathing, PLB, nPEP and oPEP in patient-1 were 1.7, 14, 4.5, and 7.3 mmHg, in patient-2; 2.3, 8, 8.3, and 12 mmHg, and in patient-3; 1, 15, unobtainable, and 9 mmHg, respectively. Maximal reduction in BORG scores occurred with PLB in patient 1 and with oPEP in patients 2 and 3. After 1 week mean SGRQ-C scores declined by 17-points. Conclusions: Upper airway manometry directly measures laryngopharyngeal pressures during rest and exercise and can be used to select and optimize PEP breathing techniques to improve respiratory symptoms in EDAC patients. Highlights: By limiting expiratory flow, EDAC causes dyspnea and reduces quality of life. Positive pressure by CPAP prevents airway collapse and improves symptoms in EDAC. Esophageal manometer measures pharyngeal pressure in various conditions & therapies. PLB, oPEP and nPEP caused varying elevations in airway pressures in each participant. PEP breathing modalities improve dyspnea and quality of life in patients with EDAC.